A Trifunctional Linker for Purified 3D Assembled Peptide Structure Arrays. Issue 2 (6th December 2017) - Mattes, Daniela S.; Rentschler, Simone; Foertsch, Tobias C.; Münch, Stephan W.; Loeffler, Felix F.; Nesterov‐Mueller, Alexander; Bräse, Stefan; Breitling, Frank
Abstract: Microarrays are an important tool in modern research that allow the rapid screening of many different interactions simultaneously. Peptide arrays, which bear different peptides arranged in separate spots, permit high‐throughput screening to investigate linear and cyclic binding sites. To study conformational or discontinuous binding sites, protein arrays are the major choice. However, the tremendous costs for the generation of high‐density protein arrays of high purity restrict progress in protein research. Therefore, peptide‐based arrays, which can mimic assembled peptide structures, have an enormous potential. Here, a method is presented to create such structures in the array format as an alternative to protein arrays. A trifunctional linker is developed with an azide, a protected alkyne, and a carboxyl group, which can react with two or three different peptides. Due to the spatial proximity, the peptides interact and can form an assembled peptide structure. As a proof of concept, assembled peptide structures are demonstrated on beads and on a polymer surface and the approach can be validated via matrix‐assisted laser desorption/ionization spectrometry. Furthermore, a multistep transfer of peptide arrays is shown, generating purified assembled peptide structure arrays in high density. Abstract : Purified and cost‐efficient assembled peptide structures with peptide arrays are created by a new method, which is presented. A trifunctional linker bearing three different functional groups can react with up to three different peptides, which offer great potential to investigate complex binding sites of proteins. As a proof of concept, assembled peptide structures on beads and 3D polymer surfaces are demonstrated and validated via mass spectrometry.